2021
DOI: 10.1007/s00259-020-05182-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the diagnostic performance and impact on management of 18F-FDG PET/CT and whole-body MRI in multiple myeloma

Abstract: Purpose Comparative data on the impact of imaging on management is lacking for multiple myeloma. This study compared the diagnostic performance and impact on management of 18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) and whole-body magnetic resonance imaging (WBMRI) in treatment-naive myeloma. Methods Forty-six patients undergoing 18F-FDG PET/CT and WBMRI were reviewed by a nuclear medicine physician and radiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 28 publications
(26 reference statements)
2
14
0
1
Order By: Relevance
“…Approaches such as comparison of WB FDG PET/CT against standard MRI of the spine and pelvis without diffusion-weighted imaging have previously shown no difference in lesion detection (32). However, our analysis is in line with results reported for retrospective series and a recent prospective study (18) comparing WB-MRI with FDG PET/CT; our work and others' firmly support wider use of WB-MRI for myeloma (17,33). This is further supported by published evidence on high interobserver agreement in WB-MRI reporting (34,35), interpretation of potential false-positive findings, and established international consensus criteria (15), together positioning WB-MRI as a new imaging standard for myeloma.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Approaches such as comparison of WB FDG PET/CT against standard MRI of the spine and pelvis without diffusion-weighted imaging have previously shown no difference in lesion detection (32). However, our analysis is in line with results reported for retrospective series and a recent prospective study (18) comparing WB-MRI with FDG PET/CT; our work and others' firmly support wider use of WB-MRI for myeloma (17,33). This is further supported by published evidence on high interobserver agreement in WB-MRI reporting (34,35), interpretation of potential false-positive findings, and established international consensus criteria (15), together positioning WB-MRI as a new imaging standard for myeloma.…”
Section: Discussionsupporting
confidence: 91%
“…Unfortunately, MRI studies that have not included diffusion-weighted sequences cannot reliably distinguish active from inactive sites and are prone to false-positive findings. One recent prospective study (18) compared WB-MRI, including diffusion-weighted MRI, with FDG PET/CT, and WB-MRI was found to have a higher sensitivity for detecting focal bone lesions. Hence, further confirmation of WB-MRI with diffusion-weighted MRI as a staging tool in myeloma will help to establish its wider deployment in clinical practice.…”
Section: Participant Samplementioning
confidence: 99%
“…Similar results were found by two other recent studies (43,44). It was also shown that CT helps improve the diagnosis of bone involvement in patients with a low 18 F-FDG uptake (44,45). Comparison of the detectability of FLs showed that, overall, DW-MRI detects more FLs than does 18 F-FDG PET/CT (44)(45)(46).…”
Section: F-fdg Pet/ct Compared With Diffusion-weighted Mri For Baseli...supporting
confidence: 85%
“…Highly cellular tissues such as tumors (where water diffusion is restricted), or tissues where the proportion of water density is higher than cellular density (such as in a cerebral infarction), result in high signal intensity on DWI with high b -values compared to the normal surrounding tissue. In patients with MM, the use of WB-DWI in diagnosis is superior to whole-body radiographs 4 and is equal to or more sensitive than PET/CT for the detection of focal lesions 1 , 5 , 6 . Although WB-DWI is mainly used in diagnostic process, there are several reports regarding the use of WB-DWI to monitor the patient’s response to treatment 7 9 .…”
Section: Introductionmentioning
confidence: 99%